Pengaruh Penerapan Good Corporate Governance dan Struktur Kepemilikan terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Non Keuangan - Ninda Novita Yoza; Efrizal Syofyan (Universitas Negeri Padang, 2021)
This study aims to determine the effect of implementing good corporate governance and ownership structure on company profitability. The independent variables are the board of commissioners, the board of directors, the audit committee, managerial ownership, and institutional ownership. While the dependent variable is the company's profitability. The sample used is non-financial companies in the infrastructure, utilities, and transportation sectors listed on the Indonesia Stock Exchange in 2017-2019. The statistical method used is multiple linear regression analysis. The results showed that the board of commissioners had a negative and insignificant effect on the company's profitability, the board of directors and the audit committee had a positive and significant effect on the company's profitability, managerial ownership and institutional ownership had a positive and insignificant effect on the company's profitability.